(untitled) (Research, Society and Development, 2021)
Objetive: to evaluate the use drugs by individuals hospitalized due to non-lethal physical trauma. Methods: prospective study carried out on a transversal cohort by assessing secondary data and toxicological analyses in a hospital of a municipality of Southern Brazil. Individuals were selected after being hospitalized due to trauma likely to be caused by drug abuse. There were assessing cases reported by public and private basic health care systems registered by the Center for Control of Intoxications, which were identified by clinical criteria or due to reports from the subjects. Biological samples were obteined for toxicological trialing. Results: nine cases (17.7%) were consideraded moderate or severe by the Glasgow trauma scale,and results obtained using the Revisited Trauma Score system indicated three cases (6.7%) as oderate or severe. The most severe cases involved individuals aged 20 to 39. Quantitative analysis f ethanol determined its presence in all samples, and at toxic levels in 15.8% of the biological amples assessed. Nine subjects had used cannabis (15.8%) and five had used cocaine (8.8%) in association with ethanol. Conclusion: the high incidence of drug use in the assessed subjects confirms the relation between drug abuse and increased risk for physical traumas.